The Effect of Seawater on The Compressive Strength and Split Tensile Strength in Self Compacting Geopolymer Concrete - Herwina Rahayu Putri; Firman Paledung; Erniati Bachtiar; Popy Indrayani (Litbang Pemas - Universitas Islam Lamongan, 2021)
Fly ash is a kind of trash that may degrade the quality of the air. As a result, it is critical that it be used as an ecologically beneficial material. Although cement is the most often used construction material, its manufacturing generates carbon dioxide, which may degrade air quality. The aim of this research was to evaluate the compressive strength and split tensile strength of self-compacting geopolymer concrete (SCGC) cured in seawater, as well as to compare SCGC with and without saltwater. In this research, a cylindrical specimen with a diameter of 10 cm and a height of 20 cm was utilized as the specimen. Fly ash is used in proportion to fine and coarse aggregates at a ratio of 1: 0.65: 1.5. Using a 0.4 activator to binder ratio. The molarity ranges utilized were 11 M, 12 M, 13 M, 14 M, and 15 M. Compressive strength and split tensile strength tests were conducted on 28-day-old concrete. The findings indicated that when the molarity of SCGC treated with seawater increased from 11 to 15 M, the compressive and split tensile strengths increased. Compressive strength values were greatest in SCGC treated at room temperature when an activator of 13 M was used, and compressive strength values dropped in SCGC treated at room temperature when an activator greater than 13 M was used